A network coding protocol for wireless sensor fog computing. (15th May 2019) - Marques, Bruno; Coelho, Igor Machado; Sena, Alexandre Da Costa; Castro, Maria Clicia
A communication protocol for fog computing should be efficient, lightweight and customisable, enabling the computing results on the edges to be passed easily through the network. In this work, we focus on a communication protocol for fog nodes in a network composed of wireless sensors, which are autonomous and spatially distributed for monitoring physical or environmental conditions. Problems with data congestion and limited physical resources are common in these networks. For the optimisation of data flow, it is important to apply techniques that reduce the transmitted data. We propose a network coding technique and study its efficiency for data transmission protocols. The experiments were performed through a wireless sensors programming framework with TinyOS operating system, NesC language and TOSSIM simulator. Experimental results demonstrate a better performance when the network coding technique is applied to the data communication protocol, for different scenarios. Further results demonstrate the network coding efficiency for fog computing, with around 80% of the total messages exchanged compared to a traditional protocol.